Investigation of Effective Parameters onto Swelling Behaviour of Superabsorbent Hydrogels - Soleimani, Fatemeh; Sadeghi, Hossein; Shahsavari, Hadis; Soleimani, Arezou; Sadeghi, Fatemeh (Asian Journal of Chemistry, 2013)
In this work, we investigated swelling behaviours of a novel superabsorbent hydrogel based on carboxymethylcellulose. A mechanism for the superabsorbent hydrogel formation was also suggested. The effect of methylenebisacrylamide, ammonium persulfate, carboxymethyl-cellulose concentration and MAAm/NIPAAm weight ratio on the water absorbency capacity has been investigated. The swelling variations of hydrogels were explained according to swelling theory based on the hydrogel chemical structure. The temperature-sensitivity properties of the hydrogels also make the intelligent polymers as good candidates for considering as potential carriers for bioactive agents, e.g., drugs.